Catalyst-free crosslinking modification of nata-de- coco-based bacterial cellulose nanofibers using citric acid - Salihu, Rabiu; Abd Razak, Saiful Izwan; Ahmad Zawawi, Nurliyana; Shahir, Shafinaz; Sani, Mohd Helmi; Wsoo, Mohammed Ahmad; Mat Nayan, Nadirul Hasraf (MDPI, 2021)
Bacterial cellulose (BC) has gained research attention in materials science and biomedicine due to its fascinating properties. BCs' fiber collapse phenomenon (inability to reabsorb water after dehydration) is one of the drawbacks that limit its potentials. To overcome this, a catalyst-free thermal crosslinking reaction was employed to modify the BC using citric acid (CA) without compromising the biocompatibility. Properties evaluation of the modified BC (MBC) by FTIR, XRD, SEM/EDX, TGA, and Tensile analysis confirmed the fiber crosslinking and improvement of some properties that could be advantageous for various applications. The modified nanofiber seems to maintain its inherent crystallinity and thermal stability with an increased water absorption/swelling and tensile modulus. The resulting MBC reported here can be relevant for wound dressings and tissue scaffolding.